2014
DOI: 10.1007/s10900-014-9838-6
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Mobile Phones in the Possible Transmission of Bacterial Infections in the Community

Abstract: Mobile phones have become indispensable accessories in today's life. However, they might act as fomites as they have travelled with their owner to places such as toilets, hospitals and kitchens which are loaded with microorganisms. A cross-sectional study was carried out to isolate and identify bacteria from mobile phones of volunteers in the community. A total of 192 mobile phones from 102 males and 90 females were swabbed and cultured. The bacteria were identified by gram staining and conventional biochemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
56
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 16 publications
5
56
3
Order By: Relevance
“…This was different from previous studies where not all phones were found to be contaminated, 10,11 although in these studies methods other than contact plate were used. On the other hand a study by Lee et al 12 using the agar touch method revealed bacteria in all phones.…”
Section: Resultscontrasting
confidence: 62%
“…This was different from previous studies where not all phones were found to be contaminated, 10,11 although in these studies methods other than contact plate were used. On the other hand a study by Lee et al 12 using the agar touch method revealed bacteria in all phones.…”
Section: Resultscontrasting
confidence: 62%
“…This finding is comparatively higher than our study in which 40.2% of the respondents used their mobile phones in toilets. Mobile phones can act as fomites as they are contaminated by users from areas such as toilets, hospitals and kitchens, which are burdened with microorganisms [26]. Furthermore, Giannini et al reported that hospital's toilets are the source for MRSA [27].…”
Section: Discussionmentioning
confidence: 99%
“…Some of the greatest concerns for antibiotic-resistant bacteria transmission occur in healthcare environments where contamination and transmission are possible through numerous fomites, ranging from mobile phones [89] to medical devices [90] to surgical tape [91] to doctors' handbags [92]. While it has been hypothesized that many of these fomites have been important sources, closer investigation often reveals a more nuanced understanding.…”
Section: Antibiotic-resistant Bacteriamentioning
confidence: 99%